2014
DOI: 10.1186/1742-2094-11-66
|View full text |Cite
|
Sign up to set email alerts
|

Co-grafting of neural stem cells with olfactory en sheathing cells promotes neuronal restoration in traumatic brain injury with an anti-inflammatory mechanism

Abstract: BackgroundWe sought to investigate the effects of co-grafting neural stem cells (NSCs) with olfactory ensheathing cells (OECs) on neurological behavior in rats subjected to traumatic brain injury (TBI) and explore underlying molecular mechanisms.MethodsTBI was established by percussion device made through a weight drop (50 g) from a 30 cm height. Cultured NSCs and OECs isolated from rats were labeled by Hoechst 33342 (blue) and chloromethyl-benzamidodialkyl carbocyanine (CM-Dil) (red), respectively. Then, NSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 32 publications
1
31
0
2
Order By: Relevance
“…Additionally, co-grafting of stem cells with another cell type has also been performed. Transplantation of NSC with olfactory ensheathing cells has been shown to result in a 3.4 fold increase in cell survival compared to NSC alone (Liu et al, 2014a). Cografting BM-MSC with Schwann cells has been reported to have effects separate from just changes in survival.…”
Section: Engraftmentmentioning
confidence: 98%
“…Additionally, co-grafting of stem cells with another cell type has also been performed. Transplantation of NSC with olfactory ensheathing cells has been shown to result in a 3.4 fold increase in cell survival compared to NSC alone (Liu et al, 2014a). Cografting BM-MSC with Schwann cells has been reported to have effects separate from just changes in survival.…”
Section: Engraftmentmentioning
confidence: 98%
“…7 Stem cell transplantation is a promising candidate to treat SCI. [8][9][10][11][12] Recent work showed that stem cells, such as mesenchymal stem cells (MSCs), [13][14][15] neural stem/progenitor cells (NS/ PCs), 16,17 and embryonic stem cells (ESCs), [18][19][20] have immunoregulatory capacity and anti-inflammatory effects and could enhance functional improvement through inducing macrophages M1/M2 phenotype transformation post SCI. This review will discuss 1) the general feature of macrophages in response to SCI, 2) the phenotype and function of macrophages in SCI, and 3) the effects of stem cells on macrophage polarization and its role in stem cell-based therapies for SCI.…”
Section: Introductionmentioning
confidence: 99%
“…showing optimal effects of co-grafting NSCs with OECs in terms of promoting NSC survival and neuronal restoration after experimental traumatic brain injury and Parkinson's disease [29,30] .…”
Section: Discussionmentioning
confidence: 99%